Prevalence of Restless Legs Syndrome among Medical Students of Karachi: An Experience from a Developing Country. (19th February 2020) - Ishaq, M.; Riaz, S. U.; Iqbal, N.; Siddiqui, S.; Moin, A.; Sajjad, S.; Ali, T.; Jamali, S.
Abstract : Background . Restless legs syndrome (RLS) is a neurological disorder characterized by an uncomfortable sensation in the legs which gets worse in the evening or night, relieved upon movement. The aim of this study was to specify the prevalence of RLS in the group of young medical students and to assess the effect of RLS on sleep, as sleep disturbance is one of the chief complaints of RLS patients. We also studied its association with smoking as it is considered an aggravating factor. Method . This was a cross-sectional study conducted from June 2017 to July 2018 in Karachi. A total of 300 students (220 females and 80 males) participated and were given questionnaires to detect RLS based on criteria proposed by the International Restless Legs Syndrome Study Group. Subjects who were positive for RLS were further asked questions about sleep by using the Epworth Sleepiness Scale and severity of RLS by using RLS Rating Scale. They were also asked about their smoking status. Results . The frequency of RLS is 8% among young adults. Out of 300 medical students, 24 students were classified positive for RLS with a female preponderance (66.7% were females and 33.3% were males). The severity of RLS was more rated to be mild to moderate. The effect of RLS on sleep was in the mild range. The p value of smoking status comparing with gender came out to be <0.001, and p value of RLS is 0.773. Conclusion . It is concluded that we found RLS to be present significantly in our population that is without comorbidities. Our results showed female preponderance and a mild sleep disturbance in our study population. More attention is needed to recognize RLS and to manage the aggravating factors of RLS.